Reproducible Risk Assessment. Issue 10 (October 2016) - Haas, Charles N.
Abstract : Reproducible research is a concept that has emerged in data and computationally intensive sciences in which the code used to conduct all analyses, including generation of publication quality figures, is directly available, and preferably in open source manner. This perspective outlines the processes and attributes, and illustrates the execution of reproducible research via a simple exposure assessment of air pollutants in metropolitan Philadelphia.